The Effect of Post Mortem Ageing and Muscle Type on Spent Hen Meat Quality : 10.5958/2581-6616.2020.00012.2 - M, Kiran; Kapase, Gangadhar; Kulkarni, Shrikant; kumar, Manoj; lakshmi, Vijaya (Journal of Meat Science, 2020)
Current investigation was carried out to study the changes in meat quality during ageing of thigh and breast muscles from spent hen meat at 4 °C. The pH of thigh muscle found to be higher (6.02) than breast muscle (5.78) throughout the ageing period. Water holding capacity increased (P<0.05) from 17.33% to 23.33 % and 33.33% to 38.33% in thigh and breast muscles, respectively. Variation (P<0.05) in protein extractability was observed throughout the ageing period. The % metmyoglobin increased (P<0.05) in thigh and breast muscles of spent hen meat. Myofibrillar fragmentation index was significantly (P<0.05) higher at 6 days of ageing in thigh and breast muscles compared to other ageing period. The metabolic activity as indicated by R Value increased progressively up to 6 days in both muscles. The SDS PAGE pattern of proteins at different ageing period as analyzed by Gel Analyzer showed appearance of few new bands on completion of ageing. The differentially expressed proteins were identified to be Vesicle associated membrane protein-7, Cartilage matrix protein, ProteinFAM210A and Phosphoglycerate mutase1, which are proposed to be generated during ageing. Present study indicates the quality changes and improvement in tenderness of thigh and breast muscles of spent hen meat during ageing.